Exploration and Identification of Arbuscular Mycorrhizal Fungi (AMF) in the Rhizosphere of Cocoa (Theobroma cacao. L) in West Sumatra - Meisilva Erona Sitepu; Winda Purnama Sari; Indra Dwipa (JERAMI : Indonesian Journal of Crop Science, 2021)
West Sumatra was declared as a center for Indonesian cocoa in the western portion. Almost all areas in West Sumatra are suitable for cocoa cultivation, so the cocoa planting area covers almost all the districts in the province. However, West Sumatran Cocoa production decline occurs because cocoa plantations are still mostly cultivated with smallholder plantations. The occurrence of land conversion and reduced land carrying capacity, including soil fertility, is due to the continuous use of inorganic fertilizers, which results in a decrease in the ecological quality of the land. Efforts to improve land conditions biologically by utilizing soil biotechnology. One of the soil microbes that can be utilized is Arbuscular Mycorrhizal Fungi (AMF). AMF that live in a symbiotic mutualism with plant roots and helps the absorption of plant nutrients and live in various places. The study aimed to identify arbuscular mycorrhiza Cocoa rhizosphere three districts, West Sumatra province, from the month of November 2020 to May 2021. The results showed the number of spores and diversity of AMF. The number of spores was 67-218 spores per 20 g soil. The root colonization was in the range of 21.3 - 24.6%. While the AMF diversity before trapped found three types of sport Glomus sp., Acaulospora sp., dan Gigaspora sp